Multifunctional inulin tethered silver-graphene quantum dots nanotheranostic module for pancreatic cancer therapy - Joshi, Preeti Nigam; Agawane, Sachin; Agawane, Sachin; Agawane, Sachin; Sarkar, Dhiman; Sarkar, Dhiman (Material Science and Engineering C- Materials for Biological Application, 2017)
Cancer nanotechnology is an emerging area of cancer diagnosis and therapy. Although considerable progress has been made for targeted drug delivery systems to deliver anticancer agents to particular site of interest, new nanomaterials are frequently being developed and explored for better drug delivery efficiency. In the present work, we have explored a novel nanoformulation based on silver-graphene quantum dots (Ag-GQDs) nanocomposite for its successful implementation for pancreatic cancer specific drug delivery in wistar rats. Carboxymethyl inulin (CMI); a modified variant of natural polysaccharide inulin is tethered with the nanocomposite via carbodiimide coupling to enhance the biocompatibility of nanoformulation. Experiments are performed to investigate the cytotoxicity reduction of silver nanoparticles after inulin tethering as well as anticancer efficacy of the system using 5-Fluorouracil (5-FU) as model drug. SEM, TEM, FT-IR, UV-vis, photoluminescence and anti proliferative assays (MTT) are performed for characterisation of the nanocomposite. Hyaluronic acid (HA) is conjugated as targeting moiety for CD-44 (cancer stem cell marker) to fabricate a complete targeted drug delivery vehicle specific for pancreatic cancer. In the present work two prime objectives were achieved; mitigation the toxicity of silver nanoparticles by inulin coating and it's in vivo application for pancreatic cancer. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: acid; Dextran; Drug-delivery; graphene quantum dots; Inulin; Nanocomposite; Nanocomposites; Nanoparticles; Pancreatic Cancer; Silver nanoparticle; Strategies; Systems; Targeted Drug Delivery

Formulation and evaluation of wound healing activity of sophorolipid-sericin gel in wistar rats - More, V. Snehal; Koratkar, Santosh S.; Kadam, Navnath; Agawane, Sachin; Prabhune, Asmita (Pharmacognosy Magazine, 2019)
Sericin is a useful by-product of silk processing and is resistant to oxidation and ultraviolet and can absorb and release moisture easily. Sericin has biological activities such as antibacterial, antioxidant, and tyrosinase inhibition. Sophorolipids are microbial extracellular glycolipids produced by resting cells of Candida bombicola. Sophorolipids show excellent skin compatibility and also have antibacterial property. In this study, we have developed a novel formulation consisting of sericin and sophorolipid with calcium alginate as a binding agent. Since both the ingredients are biocompatible and biodegradable, the formulation was tested for wound healing in Wistar rats. A commercial ointment povidone was used as control. The animal group, treated with sericin and sophorolipid cream, showed fast contraction, rapid closure, and healing when compared with control and commercial ointment. These observations were validated with histopathological studies where more fibroblast proliferation, angiogenesis, and keratinization were observed. This is a green, cost-effective formulation for fast wound healing.
Keywords: Biocompatibility; formulation; sericin; Sophorolipid; wound Healing

Metagenome sequencing to unveil microbial community composition and prevalence of antibiotic and metal resistance genes in hypersaline and hyperalkaline Lonar Lake, India - Chakraborty, Jaya; Sapkale, Vibhavari; Shah, Manan; Rajput, Vinay; Mehetre, Gajanan; Agawane, Sachin; Kamble, Sanjay; Dharne, Mahesh (Ecological Indicators, 2020)
Lonar Lake (India) is a hyperalkaline and hypersaline soda lake encompassing unique microbial composition and functions. This ecosystem has not been explored for taxonomic diversity and functional aspects (with emphasis on antibiotic and metal resistance genes) using whole metagenome sequencing for multiple years. Bacterial diversity analysis during year 2013, 2016, and 2018 depicted differences in the dominance of Proteobacteria, Firmicutes and Bacteroidetes. For archaeal diversity, a similar pattern persisted with higher abundance of Euryarchaeota. Functional metagenome analyses, indicated presence of antibiotic resistance gene (ARG) and metal resistance gene (MRG) profiles in the lake. A wider continuum of resistance genes with dominant ARG types as multidrug resistance efflux pumps and beta-lactams were also observed. The lake resistome demonstrated fluoroquinolone and acriflavine resistance genes indicating sewage water contamination in the lake. The MRGs linked with resistance to toxic metals (arsenic, cobalt, cadmium, copper, and zinc) and cation efflux protein CusA and cobalt-zinc-cadmium resistance protein revealed metal contamination. This study could be a baseline for understanding prevalence of antibiotic and metal resistance mechanisms resulting from various anthropogenic activities nearby lake, and find integrated approaches for conservation of the precious Lonar Lake ecosystem.
Keywords: Archaeal diversity; ARGs; Bacterial diversity; Illumina sequencing; Lonar lake; MRGs

Behavioral and proteomic studies reveal methylglyoxal activate pathways associated with alzheimer’s disease - Patil, Gouri; Kulsange, Shabda; Kazi, Rubina; Chirmade, Tejas; Kale, Vaikhari; Mote, Chandrashekhar; Aswar, Manoj; Koratkar, Santosh; Agawane, Sachin; Kulkarni, Mahesh (ACS Pharmacology & Translational Science, 2022)
Diabetes is one of the major risk factors for Alzheimer’s disease (AD) development. The role of elevated levels of glucose, methylglyoxal (MGO), and advanced glycation end products (AGEs) in the pathogenesis of AD is not well understood. In this pursuit, we studied the role of methylglyoxal in the pathogenesis of AD in rat models. The elevated plus-maze (EPM) behavioral study indicated that MGO induces anxiety. Treatment of telmisartan (RAGE expression inhibitor) and aminoguanidine (MGO quencher) attenuated MGO induced anxiety. Further, hippocampal proteomics demonstrated that MGO treated rats differentially regulate proteins involved in calcium homeostasis, mitochondrial functioning, and apoptosis, which may affect neurotransmission and neuronal plasticity. The hippocampal tau phosphorylation level was increased in MGO treated rats, which was reduced in the presence of aminoguanidine and telmisartan. The plasma fructosamine level was increased upon MGO treatment. Hippocampal histochemistry showed vascular degeneration and neuronal loss upon MGO treatment. This study provides mechanistic insight into the role of MGO in the diabetes-associated development of AD.

Superior processability of Antheraea mylitta silk with cryo-milling: performance in bone tissue regeneration - Parekh, Nimisha; Bijosh, C. K.; Kane, Kartiki; Panicker, Alaka; Nisal, Anuya; Wangikar, Pralhad; Agawane, Sachin (International Journal of Biological Macromolecules, 2022)
Non-mulberry silk polymers have a promising future in biomedical applications. However, the dissolution of nonmulberry silk fiber is a still challenge and this poor processability has limited the use of this material. Here, we report a unique protocol to process the Antheraea mylitta (AM) silk fiber. We have shown that the cryo-milling of silk fiber reduces the beta sheet content by more than 10% and results in an SF powder that completely dissolves in routine solvents like trifluoroacetic acid (TFA) within few hours to form highly concentrated solutions (\~20 wt %). Further, these solutions can be processed using conventional processing techniques such as electrospinning to form 3D scaffolds. Bombyx mori (BM) silk was used as a control sample in the study. In-vitro studies were also performed to monitor cell adhesion and proliferation and hMSCs differentiation into osteogenic lineage. Finally, the osteogenic potential of the scaffolds was also evaluated by a 4-week implantation study in rat calvarial model. The in-vitro and in-vivo results show that the processing techniques do not affect the biocompatibility of the material and the AM scaffolds support bone regeneration. Our results, thus, show that cryo-milling facilitates enhanced processability of non-mulberry silk and therefore expands its potential in biomedical applications.
Keywords: Bone tissue engineering; Calvarial defect; hMSCs; Non-mulberry silk fiber; Processing technique